DEVELOPMENT STRATEGY TOURISM TIKUS ISLAND BENGKULU PROVINCE WITH SWOT ANALYSIS - Herlin Herlin; Rina Trisna Yati (AFEBI Management and Business Review, 2019)
The purpose of this study was to find out how the strategy of developing Tikus island of Bengkulu province tourism. This type of research is a descriptive exploratory study, using primary (observation and questionnaire) and secondary data obtained by the Bengkulu Province Tourism Office, with samples in this study totaling 125 people. Methods of data analysis using SWOT Analysis. Based on the results of the SWOT analysis (Strenghts, Weakness, Opportunity and Treaths) showed that the strategy of developing Tikus Island Bengkulu province consisting of internal strategic factors (IFAS) consisting of Strength (S) and Weakness (W) obtained a total score of 4.28, this means that the attraction Tikus Island Bengkulu province has a strength that is greater than weakness. Whereas external factors (EFAS), which consist of opportunities and Threats (T) with a total score of 4.25 and opportunities (O) of 2.32, which means that the attraction Tikus Island Bengkulu province has a greater opportunity from threats. The meeting point between strengths, weaknesses, opportunities and threats is in quadrant I, which means that the strategy implemented is to support aggressive strategy. In this quadrant I shows that attractions Tikus Island Bengkulu province have equal opportunities and Weakness (W) so that the strategy that can be applied is to support aggressive policies (Growth Oriented Strategy, namely by developing transportation and supporting facilities to the region).